2021
DOI: 10.3390/ijerph18189544
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Bruxism in Children: Etiology, Diagnosis, and Treatment—A Literature Review

Abstract: (1) Background: Bruxism, a condition characterized by grinding and involuntary clenching of the teeth, is a risk factor for the development of masticatory dysfunction. It can occur together with sleep disturbances and may be associated with abnormal body movements, breathing difficulties, increased muscle activity, and heart rate disturbances. This disorder is becoming an important dental concern in children. (2) Methods: A literature review was carried out based on a search in PubMed and Google Scholar databa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
69
1
32

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(103 citation statements)
references
References 37 publications
1
69
1
32
Order By: Relevance
“…It is called sleep bruxism (SB) when it occurs during sleep and awake bruxism (AB) when it occurs during wakefulness [1]. This condition was first described in the literature at the beginning of the 20th century and has been the subject of numerous studies since then [2]. Later on, Lobbezoo et al made revised the definition and suggested that AB and SB should be considered different behaviors that occur during wakefulness and during sleep and that bruxism should not be considered as a disorder in otherwise healthy individuals but rather as a behavior or a physiological phenomenon, that could pose a risk factor for certain clinical consequences [3].…”
Section: Introductionmentioning
confidence: 99%
“…It is called sleep bruxism (SB) when it occurs during sleep and awake bruxism (AB) when it occurs during wakefulness [1]. This condition was first described in the literature at the beginning of the 20th century and has been the subject of numerous studies since then [2]. Later on, Lobbezoo et al made revised the definition and suggested that AB and SB should be considered different behaviors that occur during wakefulness and during sleep and that bruxism should not be considered as a disorder in otherwise healthy individuals but rather as a behavior or a physiological phenomenon, that could pose a risk factor for certain clinical consequences [3].…”
Section: Introductionmentioning
confidence: 99%
“…La etiología del bruxismo es compleja y de naturaleza multifactorial, puede ser local, sistémica, psicológica, o hereditaria (Bulanda et al, 2021;Calvano Küchler et al, 2020;Goettems et al, 2017;Lamenha Lins et al, 2020;Serra-Negra et al, 2017). Estudios refieren que la regulación del bruxismo nocturno es principalmente centralizada que, aunque en sí el bruxismo no se considera como patología o trastorno, podría ser una posible alarma o síntoma de condiciones de salud o hábitos que perturban el sistema nervioso central (Restrepo, Santamaría, et al, 2021).…”
Section: Etiologíaunclassified
“…La relevancia clínica de este hábito ha sido relacionada como posible causante de: desgaste y daño de las piezas dentales, abfracciones, dolor de cabeza y otros trastornos temporomandibulares (Berger et al, 2017;Poojary et al, 2018). Sumado a otros factores para diagnosticar esta afección existen diversos métodos de evaluación que permiten determinar un adecuado diagnóstico y consecuentemente establecer un plan de tratamiento para el paciente (Berger et al, 2017;Bulanda et al, 2021).…”
Section: Introductionunclassified
“…Barbosa et al [ 10 ] found that the prevalence of sleep bruxism (SB) in childhood and adolescence ranges between 7.0% and 15.1%, with girls being more frequently affected. The aetiology of bruxism results from a complex interaction between peripheral (morphological) and central (pathophysiological and psychological) variables [ 21 , 22 , 23 ]. It has also been reported that in younger children, the immaturity of the masticatory neuromuscular system may play a role [ 10 ].…”
Section: Introductionmentioning
confidence: 99%